DEPTH-DISTRIBUTION PATTERN OF ORGANIC CARBON ALONG RIVER JAKARA: APPLICATION OF EQUAL-AREA SPLINES TO URBAN AGRICULTURAL SOILS USING R. (FUDMA JOURNAL OF SCIENCES, 2023)
This research was conducted along the bank of River Jakara in metropolitan Kano, Kano state, Nigeria (latitude 11º 25' N and 12º 47' N and longitude 8º 22' E to 8º 39' E and lies 472m elevation). Three profile pits were sunk and four soil samples were collected according to profile depth of 30 cm intervals (0-30, 30-60, 60-90, and 90-120 cm). The research aimed to assess the fitness and validity of the equal-area spline functions on vertical distribution of organic carbon in the study area. The algorithm (one profile function) displayed organic carbon (OC g/kg) content decreased down the profile depth across all the three soil pits. The fitness and validity of the model (R2) ranged in the order 0.85, 0.93 and 0.94 with RMSE of 2.09, 1.47 and 1.32 respectively between the measured and predicted organic carbon value in the study area
Keywords: Population, natural resources, urban growth